Perceptions and Difficulties of Distance Learning Among Beginning Teachers and Kindergarteners During the Covid-19 Pandemic Period - Zedan, Raed (Alberta Journal of Educational Research, 2024)
Exploring the perceptions and challenges faced by beginning teachers and kindergarten teachers in the realm of distance learning reveals critical insights into the evolving landscape of early education in a digital age. The present study explored the challenges and difficulties experienced by beginning teachers and kindergarteners in the context of distance learning. Qualitative research was conducted through semi-structured interviews involving 254 novice teachers and kindergarten educators. The findings revealed a range of difficulties new teachers face in the distance learning environment. These included challenges in conveying educational content, issues with Wi-Fi and internet connectivity, a lack of resources and technological tools, difficulties in engaging students in Zoom meetings, poor communication between teachers and students, insufficient preparation and training for distance teaching, inadequate digital skills, and a lack of experience among parents with the new method of learning. Understanding the challenges and difficulties that novice teachers encounter, particularly during their initial professional years and in exceptional circumstances like the COVID-19 pandemic, is crucial. This understanding not only aids in addressing and surmounting these challenges but also contributes to the enhancement and development of current distance teaching models. Such improvements should consider the specific needs and challenges of new teachers.